FAKTOR-FAKTOR INDIVIDU YANG MEMENGARUHI KEPATUHAN PERAWAT PADA PROSEDUR PENGELOLAAN LIMBAH MEDIS PADAT DI RS TIPE C KECAMATAN BAREGBEG TAHUN 2021 - Kinanti Adiefa, Astari (2021)
As the number of hospitals grows, so does the quantity of medical waste produced increases significantly, especially in the time of COVID-19 pandemic, by 30-50 percent. Improper management can make many consequences, including an increase in the risk of a work accident due to solid medical waste for health workers. The purpose of this research is to discover the correlation and influence of education level, knowledge, years of service, and workload on nurses' compliance with hospital solid medical waste management procedures. The cross-sectional study was used as a research design in a sample of 83 nurses at Type C Hospital, Baregbeg District, collected using a total sampling method from a questionnaire. According to the study's findings, the univariate analysis showed that 44 nurses (53%) had a diploma level of education, 39 nurses (47.0%) had moderate knowledge, 49 nurses (59%) had a tenure of < 2 years, 49 nurses (59, 0%) have a moderate workload, and 48 respondents (57.8%) comply with solid medical waste management procedures. The bivariate analysis results revealed that there was a link between education level (p = 0.028), knowledge (p = 0.019), and workload (p = 0.000). On the other hand, there was no relationship between years of service (p = 0.406) and nurse compliance with solid medical waste management procedures. According to the findings of the multivariate analysis, workload had an influence and became the most dominant variable affecting nurses' adherence, implying that the heavier the workload, the lower the compliance with solid medical waste management procedures (p = 0.000; OR = 9.954; 95% CI = 3.030 - 32.701).